2022
DOI: 10.1112/plms.12464
|View full text |Cite
|
Sign up to set email alerts
|

Higher Du Bois singularities of hypersurfaces

Abstract: For a complex algebraic variety 𝑋, we introduce higher 𝑝-Du Bois singularity by imposing canonical isomorphisms between the sheaves of KΓ€hler differential forms Ξ© π‘ž 𝑋 and the shifted graded pieces of the Du Bois complex Ξ© π‘ž 𝑋 for π‘ž β©½ 𝑝. If 𝑋 is a reduced hypersurface, we show that higher 𝑝-Du Bois singularity coincides with higher 𝑝-log canonical singularity, generalizing a well-known M S C 2 0 2 0 14B05, 14F10, 14F17, 32S35 (primary)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…We also obtain local vanishing results for sheaves of forms with log poles associated to such a resolution, generalising Nakano-type results in [52] and [36]. We prove a vanishing result for cohomologies of the graded pieces of the Du Bois complex when Z is a local complete intersection, extending the study of higher Du Bois singularities of hypersurfaces in [41] and [24]. When Z has isolated singularities, we refine a result in [25] on the coincidence of h-differentials and reflexive differentials, for forms of low degree.…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…We also obtain local vanishing results for sheaves of forms with log poles associated to such a resolution, generalising Nakano-type results in [52] and [36]. We prove a vanishing result for cohomologies of the graded pieces of the Du Bois complex when Z is a local complete intersection, extending the study of higher Du Bois singularities of hypersurfaces in [41] and [24]. When Z has isolated singularities, we refine a result in [25] on the coincidence of h-differentials and reflexive differentials, for forms of low degree.…”
Section: Introductionsupporting
confidence: 63%
“…The first result concerning varieties with this property was obtained in [41], where is was shown that if Z is a hypersurface whose minimal exponent is β‰₯ 𝑝 + 1, then Z has only higher p-Du Bois singularities; recall that the minimal exponent of Z, which can be defined via the Bernstein-Sato polynomial of Z, roughly describes how close the Hodge filtration and pole order filtration are on the localisation π’ͺ 𝑋 ( * 𝑍). The converse to this result was obtained in [24]. The Hodge filtration on local cohomology allows us to extend these results to all local complete intersections.…”
Section: Recall That the Du Bois Complex Ο‰ β€’mentioning
confidence: 68%
See 3 more Smart Citations